Development of inverse circadian blood pressure pattern in transgenic hypertensive Tgr(mREN2)27 rats - Witte, Klaus; Lemmer, Björn (Chronobiology international, 1999)
TGR(mREN2)27 (TGR) rats are transgenic animals with an additional mouse renin gene, which leads to overactivity of the renin-angiotensin system. Adult TGR rats are characterized by fulminant hypertension, hypertensive end-organ damage, and an inverse circadian blood pressure pattern. To study the ontogenetic development of cardiovascular circadian rhythms, telemetric blood pressure transmitters were implanted in male Sprague-Dawley (SPRD, n = 5) and heterozygous, transgenic TGR rats before 5 weeks of age. The TGR received either drinking water or enalapril 10 mg/L in drinking water (n = 5 per group). Drug intake was measured throughout the study by computerized monitoring of drinking volume. Circadian patterns in blood pressure and heart rate were analyzed from 5 to 11 weeks of age. In the first week after transmitter implantation, blood pressure did not differ among SPRD, untreated, and enalapril-treated TGR rats. In parallel with the rise in blood pressure of untreated TGR rats, a continuous delay of the circadian acrophase (time of fitted blood pressure maximum) was observed, leading to a complete reversal of the rhythm in blood pressure at an age of 8 weeks. Enalapril reduced blood pressure at night, but was less effective during the day, presumably due to the drinking pattern of the animals, which ingested about 90% of their daily water intake during the nocturnal activity period. After discontinuation of treatment, blood pressure returned almost immediately to values found in untreated TGR rats. In conclusion, the inverse circadian blood pressure profile in TGR rats develops in parallel with the increase in blood pressure. Direct effects of the brain renin-angiotensin system may be involved in the disturbed circadian rhythmicity in TGR(mREN2)27 rats.
Published online: 07 Jul 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 14.04.2022